Pertimbangan Hukum Hakim dan Perlindungan Korban Penipuan Jual Beli Online di Facebook - Regina Yustine Gultom; Radisman Saragih; Paltiada Saragi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This article analyses the judge’s considerations in Batang District Court Decision Number 6/Pid.Sus/2021/PN.BTG regarding sentencing perpetrators and providing legal protection for victims of online transaction fraud on Facebook. Employing a normative juridical research method with statutory and case approaches, this study utilizes primary legal data (including the 1945 Constitution, Criminal Code, Criminal Procedure Code, Witness and Victim Protection Law, Judicial Authority Law, and the Electronic Information and Transactions Law) alongside secondary and tertiary legal materials to underscore the crucial role of judicial deliberation in achieving just and legally certain outcomes for victims of online fraud.